Hyper-inflammatory profile and immunoparalysis in patients with severe Legionnaires’ disease - Allam, Camille; Mouton, William; Testaert, Hugo; Ginevra, Christophe; Fessy, Noémie; Ibranosyan, Marine; Descours, Ghislaine; Beraud, Laetitia; Guillemot, Johann; Chapalain, Annelise; Albert-Vega, Chloé; Richard, Jean-Christophe; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Severe Legionnaires’ disease (LD) can lead to multi-organ failure or death in 10%–30% of patients. Although hyper-inflammation and immunoparalysis are well described in sepsis and are associated with high disease severity, little is known about the immune response in LD. This study aimed to evaluate the immune status of patients with LD and its association with disease severity. Methods A total of 92 hospitalized LD patients were included; 19 plasmatic cytokines and pulmonary Legionella DNA load were measured in 84 patients on the day of inclusion (day 0, D0). Immune functional assays (IFAs) were performed from whole blood samples collected at D2 and stimulated with concanavalin A [conA, n = 19 patients and n = 21 healthy volunteers (HV)] or lipopolysaccharide (LPS, n = 14 patients and n = 9 HV). A total of 19 cytokines (conA stimulation) and TNF-α (LPS stimulation) were quantified from the supernatants. The Sequential Organ Failure Assessment (SOFA) severity score was recorded at D0 and the mechanical ventilation (MV) status was recorded at D0 and D8. Results Among the 84 patients, a higher secretion of plasmatic MCP-1, MIP1-β, IL-6, IL-8, IFN-γ, TNF-α, and IL-17 was observed in the patients with D0 and D8 MV. Multiparametric analysis showed that these seven cytokines were positively associated with the SOFA score. Upon conA stimulation, LD patients had a lower secretion capacity for 16 of the 19 quantified cytokines and a higher release of IL-18 and MCP-1 compared to HV. IL-18 secretion was higher in D0 and D8 MV patients. TNF-α secretion, measured after ex vivo LPS stimulation, was significantly reduced in LD patients and was associated with D8 MV status. Discussion The present findings describe a hyper-inflammatory phase at the initial phase of Legionella pneumonia that is more pronounced in patients with severe LD. These patients also present an immunoparalysis for a large number of cytokines, except IL-18 whose secretion is increased. An assessment of the immune response may be relevant to identify patients eligible for future innovative host-directed therapies.